(untitled) (World Science, 2020)
To date, the problem of reduced fertility is quite relevant. At the same time, it should be noted that the effectiveness of infertility treatment, even with the use of the latest techniques, tools and drugs does not exceed 35-40%. This can be explained by insufficient study of a number of causes that lead to impaired fertility. One of these little-known and poorly studied factors is pelvic venous plethora, in particular varicose veins of the ovaries. While anatomically similar disease in men - varicocele - is given great importance, in women, even the very existence of this pathology is controversial among some authors. All studies were conducted in compliance with the basic bioethical norms and requirements of the Declaration of Helsinki. 117 women of reproductive age (21 - 42 years) with infertility of functional genesis were examined. According to the results of the analysis, the clinical and anamnestic features of women with infertility and ovaric varicocele are increased proportion of patients with intellectual differentiation and psycho-emotional and physical stress, high frequency of infectious diseases with acyclic uterine bleeding, dysmenorrhea and premenstrual. Changes in the anatomical and functional state of the pelvic organs and venous system in women with infertility and ovarian varicocele have been established. It was found that the hormonal profile of women with infertility and ovarian varicocele is characterized by a decrease in estradiol and progesterone. A pathogenetically sound algorithm for the diagnosis and treatment of women with infertility and ovarian varicocele has been developed, which is based on clinical data and the results of instrumental methods of examination.